2023
DOI: 10.3390/biomedicines11102759
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Platelet-Rich Plasma and Hyaluronic Acid vs. Platelet-Rich Plasma Alone for Treatment of Knee Osteoarthritis

Ashim Gupta,
Surya Prakash Sharma,
Anish G. Potty

Abstract: Knee osteoarthritis (OA) is the most documented form of OA and is accountable for about 80% of total OA cases worldwide [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Over the last decade, there has been an increased interest in the use of autologous allografts, including platelet-rich plasma (PRP) for MSK regenerative medicine applications [18]. Numerous studies, including case reports and studies, randomized controlled trials (RCT), systematic reviews, and meta-analyses have demonstrated the safety and efficacy of PRP for MSK disorders [18][19][20][21][22]. Conversely, there are studies demonstrating subpar outcomes [18,23].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, there has been an increased interest in the use of autologous allografts, including platelet-rich plasma (PRP) for MSK regenerative medicine applications [18]. Numerous studies, including case reports and studies, randomized controlled trials (RCT), systematic reviews, and meta-analyses have demonstrated the safety and efficacy of PRP for MSK disorders [18][19][20][21][22]. Conversely, there are studies demonstrating subpar outcomes [18,23].…”
Section: Introductionmentioning
confidence: 99%
“…The knee, the most likely joint to present osteoarthritis (OA), is accountable for approximately 80% of the global burden of the OA [1,2]. The prevalence of knee OA has continued to increase over the last two decades, with no indications of slowing down [1,2].…”
mentioning
confidence: 99%
“…The knee, the most likely joint to present osteoarthritis (OA), is accountable for approximately 80% of the global burden of the OA [1,2]. The prevalence of knee OA has continued to increase over the last two decades, with no indications of slowing down [1,2]. Its etiology entails inflammation of the synovial tissue and degeneration of the articular cartilage, resulting in unendurable pain and loss of function [3,4].…”
mentioning
confidence: 99%
See 1 more Smart Citation